Composição florística e biomassa da estrato regenerativo natural de uma floresta secundária de terra firme no Distrito de Arapixuna, Santarém, Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
The objective of the present work is to evaluate the role of the natural regenerative stratum of a secondary Terra Firme forest in Arapixuna district, Santarém, Pará. There is still little work on the role of shrubs and trees that develop within a community in process. of natural regeneration. Therefore, to perform the evaluation, several parameters were considered, such as floristic composition, structure, biomass and seedling quantity. Four plots of 10m x 50m (0.2 ha) were installed in which there was already a georeferencing of the site and where the forest inventory of the tree population with diameter above 10 cm was previously carried out in Arapixuna district. Therefore, a new plant inventory was prepared in the following size classes: CT1: 0.4 m up to or equal to 1.5 m; CT 2: 1.5 m to or equal to 3.0 m; CT3: up to 3.0 m and diameter smaller than or equal to 5.0 cm and CT4: 5.0 cm with diameter between 5.0 cm to or equal to 10.0 cm and assessed the quality of natural regeneration: alive, standing and with damage. The total number of individuals inventoried was 838, of which 19 families, 28 genera and 25 botanical species were identified. The main families were Apocynaceae, Lauraceae, Euphorbiaceae, Salicaceae, Lecythidaceae and Boraginaceae. The number of seedlings was also quite high with 883 in total. Through the analysis of vertical and horizontal structure, as well as biomass quantification it was found that the various tools that the forest uses to survive enable the secondary terra firme forest to be able to regenerate naturally.
Keywords: Fitossociologia; Ecologia de florestas; Ciclos biogeoquímicos; CNPQ:: CIÊNCIAS BIOLÓGICAS